Comparison of four different lactation curve models for prediction of weekly test day milk yields in Murrah buffalos - SAHOO, SAROJ KUMAR; SINGH, AVTAR; GUPTA, A K; CHAKRAVARTY, A K; AMBHORE, G S; SINGH, MANVENDRA (The Indian Journal of Animal Sciences, 2016)
The present investigation was carried out using data on 39,059 weekly test day milk yield (WTDMY) records during first lactation of 961 Murrah buffaloes calved during 1977–2012 maintained in an organized farm at the Institute. The least squares means of the WTDMY ranged from 2.50±0.09 kg to 7.81±0.09 kg. The relative efficiency of 4 lactation curve models via gamma-type function (GF), exponential function (EF), mixed log function (MLF) and polynomial regression function (PRF) were compared. PRF described the highest coefficient of determination (99.30%) and with least value (0.02 kg) of root mean squares error (RMSE), whereas, least coefficient of determination (88.50%) was observed in EF having maximum (0.08 kg) RMSE value suggesting PRF the best mathematical model for prediction of WTDMYs in Murrah buffaloes.